PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V DI SD RODHOTUL QUR’AN EMPAT LAMPUNG SELATAN - Nur Latifah Dwitama Putri; Sri latifah; Yuli yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes in the Natural and Social Sciences (IPAS) subject among fifth-grade students at SD Rodhotul Qur’an Empat, South Lampung, which are presumed to be influenced by the use of less optimal instructional models. The purpose of this study was to examine the effect of implementing the Problem Based Learning model on students’ IPAS learning outcomes. A quantitative approach was employed using a quasi-experimental research design with a pretest–posttest control group design. The research subjects consisted of two classes: an experimental class that applied the Problem Based Learning model and a control class that used a conventional learning model, with a total of 52 students. Data were collected through learning outcome tests, observations, and documentation. The research instruments were tested for validity, reliability, item difficulty level, and discrimination index. Data analysis was conducted using normality tests, homogeneity tests, and an independent samples t-test with the assistance of IBM SPSS. The results showed that the average learning outcomes of students in the experimental class were higher than those in the control class, with a significance value of 0.000 (< 0.05). These findings indicate that the Problem Based Learning model has a significant effect on improving IPAS learning outcomes of fifth-grade students and is effective in promoting active engagement and meaningful learning.